Persepsi masyarakat tentang hukum syariah menabung di Bank dan tingkat literasi keuangan syariah - Waluya, Atep Hendang (Al-Urban: Jurnal Ekonomi Syariah dan Filantropi Islam, 2019)
This study has three objectives. First, to find out the people of Tangerang City perception about sharia law regarding saving in Islamic and conventional banks. Second, to find out their Islamic financial literacy level. And third, to determine the relationship between their perceptions and their Islamic financial literacy level. This study uses quantitative methods with primary data collected by integrating questionnaires in 13 sub-districts in the city of Tangerang. The method used to determine the number of samples is the Slovin formula, while data analysis uses the Kendall’s Tau correlation. This study produced several findings. First, the perception of the Tangerang city people about the law of saving in Islamic banks is dominated by the answer recommended, while the saving law in conventional banks according to the majority of the people of Tangerang City is permissible. Second, the level of sharia financial literacy in Tangerang City is low, with the lowest indicators are their skills in using Islamic financial services. Third, there is a strong relationship between the people of Tangerang City perception about sharia law saving in banks with the level of Islamic financial literacy.